(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2021)
The existence of park facilities as public open spaces is a phenomenon of development activities that are much done, referring to the need for interaction space for the community. The function of the park in its development cannot be separated from the historical value since the colonial era, where its existence is a form of providing green open space oriented to parks in Europe. Seeing the reality of its development, the park facilities now are not only built in the city enclave, but also penetrate into formal environments such as government offices. Bandung, Surabaya and Semarang are the 3 (three) examples of capitals in Indonesia that carried out that development, which are the City Hall complex. The two facilities located in one area can encourage issues regarding the borders of public parks which accommodate informal activities over the control of the city government center office environment structure as an existing building that accommodates formal activities. The method used in this study is descriptive qualitative through an analytical approach based on theory. The analysis is carried out by observing the landscape layout and functions since its inception in order to find out what aspects are maintained or transformed. After that, regarding the ownership of the elements of its present spatial borders. Based on research, Bandung, Surabaya, and Semarang City Hall shows that the existence of public parks in an office environment results in an arrangement that can influence the overall arrangement and user movement pattern of the environment.